Self-reported Tinnitus and Vertigo or Dizziness in a Cohort of Adult Long COVID Patients - Degen, Chantal Vanessa; Mikuteit, Marie; Niewolik, Jacqueline; Schröder, Dominik; Vahldiek, Kai; Mücke, Urs; Heinemann, Stephanie; Müller, Frank; Behrens, Georg Martin Norbert; Klawonn, Frank; Dopfer-Jablonka, Alexandra; Steffens, Sandra (Frontiers in Neurology, 2022)
Tinnitus, vertigo and dizziness are symptoms commonly reported among Long and Post COVID patients, however the severity of these symptoms has not been assessed in large trials. Therefore, in this study a large cohort of Long COVID patients was surveyed about the presence and severity of tinnitus and vertigo or dizziness symptoms. The online survey was completed by a German cohort of 1,082 adult Long COVID patients after a mean period of 43.2 weeks ± 23.4 weeks after infection. 85% were not fully vaccinated (at least two vaccinations) at the time of their first COVID symptoms and 9.8% were hospitalized in the course of their acute SARS-CoV-2 infection. At the time of the survey, 60% of patients reported the presence of vertigo or dizziness with a mean severity of 4.6 ± 2.7 on a scale of 1 (least severe) to 10 (most severe) and 30% complained of tinnitus with a mean severity of 4.8 ± 3.0. Approximately one fifth of the participants with tinnitus and vertigo or dizziness, rated their symptoms to be severe. The data shown in this study confirms that tinnitus and vertigo or dizziness are common symptoms in Long COVID patients and demonstrates, that a compelling number of patients rate their symptoms as severe. The self-reported severity highlights the need for Long COVID clinics to address these symptoms effectively. We suggest a multidisciplinary diagnostic and therapeutic approach to prevent further morbidity and socioeconomic burden for Long COVID patients suffering from severe vertigo, dizziness or tinnitus.